Adding Semantics to Electronic Business Documents Exchanged in Collaborative Commerce Relations - Rico, Mariela Guadalupe (2009)
In order to support the execution of collaborative business processes, trading partners have to exchange electronic business documents. Since each partner has its own systems and culture, they could use different terms and metadata structures to represent their data, even when referring to the same domain of interest. Then, an appropriate approach for defining the semantics of these documents is required to achieve semantic interoperability. To this aim, a number of approaches have been proposed based on the use of a single domain ontology. These approaches imply the imposition of a global meaning of terms, which are used to represent the entities of a domain. This goes in opposition to one of the aims of trading partners, which is to participate in collaborative business processes without losing their autonomy and privacy. In this scenario, it is necessary to define a framework for allowing trading partners to exchange information without imposing a global meaning of it. In this paper, a novel approach is proposed in order to define the semantics of the electronic business documents interchanged between trading partners in a collaborative relationship. This approach is based on the idea of making some domain features, which are generally implicit, explicit in the domain ontologies. An application example of this approach is also presented.